Sufficient conditions for superstability of many-body interactions - Tertychnyi, M. V. (Methods of Functional Analysis and Topology, 2008)
A detailed analysis of sufficient conditions on a family of many-body potentials, which ensure stability, superstability or strong superstability of a statistical system is given in present work.There has been given also an example of superstable many-body interaction.